Social networks and university experiences during emergency remote teaching in Costa Rica - Gómez-Montero, Paola (2022)
Changes in higher education due to the COVID-19 pandemic have affected students, including those studying at the Universidad de Costa Rica (UCR). Social networks that offer spaces for anonymous confessions are a source of information to expand knowledge of this problem, hence, the objective of this study was to identify the main topics related to the well-being, emergency online learning and the COVID-19 pandemic, expressed by students of UCR through the Facebook page Confesiones UCR, between march 6, 2020, and september 30, 2021, and the Facebook group Experiencias Virtuales UCR, between july 4, 2021, and September 30, 2021. A qualitative method was used, which consisted in the documental review of 133 publications from both virtual sites. Thematic categories were created and grouped in three dimensions: personal, interpersonal, and institutional. The data analysis showed that the situations experienced by the students not only respond to individual difficulties (predominantly anxiety and/or stress, fatigue, lack of motivation and questioning the continuity of studies) and interpersonal difficulties (the lack of support from family, friends and peers) to face the challenges of emergency remote education and maintain well-being, but also showed opportunities of improvement and institutional limitations (especially the little perceived support or interest from teachers) to face the same challenges. This study concludes that the reviewed sites facilitate relief, requests, and the exchange of support among students, in the face of these problems that affect different dimensions of well-being and contribute to the educational process.